The Effect of Supervisor Support and Work Stress on Employees’ Turnover Intention Mediated by Job Satisfaction - Muhammad Fachquroji; Ismi Darmastuti; Tutus Kenanthus Avica Putra; Dikzi Adhi Prasetya (JURNAL BISNIS STRATEGI, 2025)
This study examines the effects of supervisor support and job stress on employees’ turnover intention, with job satisfaction acting as an intervening variable, at KSP Sahabat Bintang Mandiri. A quantitative survey was conducted by distributing an SEM questionnaire (Amos v.26) to 125 permanent employees. The analysis comprised validity and reliability testing, followed by structural regression weight assessment. Results indicate that supervisor support has a significant positive effect on job satisfaction, whereas job stress exerts a significant negative impact. Furthermore, job satisfaction was found to significantly reduce employees’ turnover intentions. These findings underscore the importance of strengthening supervisory support systems and implementing effective stress management to enhance job satisfaction and mitigate turnover intention, particularly among permanent staff.